Presence of L1014F Knockdown-Resistance Mutation in Anopheles gambiae s.s. From São Tomé and Príncipe - Zhang, Hongying; Li, Mingqiang; Tan, Ruixiang; Deng, Changsheng; Huang, Bo; Wu, Zhibin; Zheng, Shaoqing; Guo, Wenfeng; Tuo, Fei; Yuan, Yueming; Bandeira, Carlos Alberto; Rompão, D’almeida Herodes; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria, one of the most serious parasitic diseases, kills thousands of people every year, especially in Africa. São Tomé and Príncipe are known to have stable transmission of malaria. Indoor residual spraying (IRS) of insecticides and long-lasting insecticidal nets (LLIN) are considered as an effective malaria control interventions in these places. The resistance status of Anopheles gambiae s.s. from Agua Grande, Caue, and Lemba of São Tomé and Príncipe to insecticides, such as dichlorodiphenyltrichloroethane (DDT) (4.0%), deltamethrin (0.05%), permethrin (0.75%), fenitrothion (1.0%), and malathion (5.0%), were tested according to the WHO standard protocol. DNA extraction, species identification, as well as kdr and ace-1R genotyping were done with the surviving and dead mosquitoes post testing. They showed resistance to cypermethrin with mortality rates ranging from 89.06% to 89.66%. Mosquitoes collected from Agua Grande, Caue, and Lemba displayed resistance to DDT and fenitrothion with mortality rates higher than 90%. No other species were detected in these study localities other than Anopheles gambiae s.s. The frequency of L1014F was high in the three investigated sites, which was detected for the first time in São Tomé and Príncipe. No ace-1R mutation was detected in all investigated sites. The high frequency of L1014F showed that kdr L1014F mutation might be related to insecticide resistance to Anopheles gambiae s.s. populations from São Tomé and Príncipe. Insecticide resistance status is alarming and, therefore, future malaria vector management should be seriously considered by the government of São Tomé and Príncipe.